Classification of Spanish white wines using their electrophoretic profiles obtained by capillary zone electrophoresis with amperometric detection. Issue 11 (10th April 2014) - Arribas, Alberto Sánchez; Martínez‐Fernández, Marta; Moreno, Mónica; Bermejo, Esperanza; Zapardiel, Antonio; Chicharro, Manuel; Cifuentes, Alejandro
<x xml:space="preserve">Abstract</x> A method was developed for the simultaneous detection of eight polyphenols (t‐resveratrol, (+)‐catechin, quercetin and p‐coumaric, caffeic, sinapic, ferulic, and gallic acids) by CZE with electrochemical detection. Separation of these polyphenols was achieved within 25 min using a 200 mM borate buffer (pH 9.4) containing 10% methanol as separation electrolyte. Amperometric detection of polyphenols was carried out with a glassy carbon electrode (GCE) modified with a multiwalled carbon nanotubes (CNT) layer obtained from a dispersion of CNT in polyethylenimine. The excellent electrochemical properties of this modified electrode allowed the detection and quantification of the selected polyphenols in white wines without any pretreatment step, showing remarkable signal stability despite the presence of potential fouling substances in wine. The electrophoretic profiles of white wines, obtained using this methodology, have proven to be useful for the classification of these wines by means of chemometric multivariate techniques. Principal component analysis and discriminant analysis allowed accurate classification of wine samples on the basis of their grape varietal (verdejo and airén) using the information contained in selected zones of the electropherogram. The utility of the proposed CZE methodology based on the electrochemical response of CNT‐modified electrodes appears to be promising in the field of wine industry and it is expected to be successfully extended to classification of a wider range of wines made of other grape varietals.